Perawatan Mesin untuk Meningkatkan Performa dan Keandalan Mesin dan Peralatan - Romiyadi, Romiyadi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Machine maintenance is a critical component in the industrial and manufacturing sectors to ensure that equipment operates efficiently and has a prolonged lifespan. This study aims to explore the various types of machine maintenance implemented across different industrial sectors, along with the benefits and challenges associated with their application. Utilizing a literature review approach, the study identifies four main types of maintenance: preventive, corrective, predictive, and redesign. Each maintenance type plays a crucial role in enhancing machine performance, reducing downtime, and extending the service life of industrial equipment. Effective maintenance practices offer several advantages, including improved operational performance, reduced repair costs, and enhanced workplace safety. However, the implementation of maintenance strategies presents several challenges, such as high costs, limited availability of skilled labor, and the time required for maintenance procedures. Despite these obstacles, with the adoption of appropriate strategies, such challenges can be effectively managed, enabling companies to achieve greater operational efficiency and long-term sustainability.